O2 plasma-modified carbon nanotube for sulfamethoxazole degradation via peroxymonosulfate activation: Synergism of radical and non-radical pathways boosting water decontamination and detoxification - Shiqi Liu; Zichen Zhang; Rui Lu; Yuankun Mao; Huiru Ge; Can Liu; Chenxi Tian; Siyuan Yin; Li Feng; Yongze Liu; Chao Chen; Liqiu Zhang (Chemosphere, 2023)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Moderate selenium alleviates the pulmonary function impairment induced by cadmium and lead in adults: A population-based study - Heze Fan; Ying Xiong; Yuzhi Huang; Lijun Wang; Chenbo Xu; Wenyuan Li; Xueying Feng; Yuxuan Yang; Rui Hua; Zihao Wang; Zuyi Yuan; Juan Zhou (Science of The Total Environment, 2023)

Accelerated aging of lithium-ion batteries: bridging battery aging analysis and operational lifetime prediction - Rui Li; Liying Bao; Lai Chen; Cheng Zha; Jingyang Dong; Nan Qi; Rui Tang; Yun Lu; Meng Wang; Rong Huang; Kang Yan; Yuefeng Su; et al. (Science Bulletin, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Three new flavones from the whole plants of Cassia auriculata Linn. and their antiviral activities - Rui-Feng Xiong; Jun-Na Zheng; Qing-Yang Wu; Ning Jiang; Yuan-Sheng He; Yong-Jun Zhang; Ben-Hui Li; Wei Li; Qiu-Fen Hu; Zhen-Yuan Xia; Yin-Ke Li (Phytochemistry Letters, 2023)

Volatile organic compounds of Bacillus spp. as an emerging antifungal resource play a significant role in fruit postharvest disease control - Lijun Ling; Yao Li; Kunling Jiang; Yuanyuan Wang; Hong Luo; Wenting Cheng; Mingmei Pang; Lijun Feng; Rui Yue; Yongpeng Zhou (Food Bioscience, 2023)

Physicochemical stability of lichenan (Usnea longissima) decorated-selenium nanoparticles for cancer chemoprevention - Ziying Yang; Yajie Hu; Panpan Yue; Rui Tian; Huiling Li; Baozhong Lü; Gegu Chen; Feng Peng (Food Bioscience, 2023)

The interaction among Kluyveromyces marxianus G-Y4, Lacticaseibacillus paracasei GL1, and Lactobacillus helveticus SNA12 and signaling molecule AI-2 participate in the formation of biofilm - Xiaomeng Wang; Kai Ma; Changliang Zhang; Feng Ji; Lili Chen; Xueliang Zhang; Ghahvechi Chaeipeima Mahsa; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Microbiology, 2023)

Molecular and functional characterization of golden pompano (Trachinotus blochii) TBK1 on IFN regulation - Jin-Feng Tong; Rui-Hai Gan; Lang Yu; Shao-Yang Bu; Jun-Long Sun; Xin Wen; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2023)

Current investigations on global N2O emissions and reductions: Prospect and outlook - Rui Feng; Zhenhua Li (Environmental Pollution, 2023)

Sources and solubility of aerosol phosphorus at a coastal site in northern China: Coarse versus fine particles and spring versus winter - Shuwei Dong; Huanhuan Zhang; Padmaja Krishnan; Shiguo Jia; Chengpeng Huang; Fu Wang; Lan Luo; Feng Wang; He Meng; Yujiao Zhu; Rui Li; Mingjin Tang (Atmospheric Environment, 2023)

Volatile organic compounds during routine production and planned shutdown of a petrochemical refinery: Emission characteristics, source and risk assessment - Yunxia Feng; Guolong Wang; Rui Dong; Bo Li; Dewu Ding; Jinchan Peng; Anshan Xiao (Atmospheric Pollution Research, 2023)

Low-dose IL-2 Treatment Rescues Cognitive Deficits by Repairing the Imbalance Between Treg and Th17 Cells at the Middle Alzheimer’s Disease Stage - Lin Yuan; Lei Xie; Hao Zhang; Yu Zhang; Yunbo Wei; Jinhong Feng; Li Cui; Rui Tian; Jia Feng; Di Yu; Cui Lv (Journal of Neuroimmune Pharmacology, 2023)

Effects of root rot on microbial communities associated with goji berry (Lycium barbarum) in the Qaidam Basin, China - Zhilin Feng; Yuancan Xiao; Na Li; Qingbo Gao; Jiuli Wang; Shi-long Chen; Rui Xing (European Journal of Plant Pathology, 2023)

Telluribacter roseus sp. nov., Isolated from the Kumtag Desert Soil - Chu-Ying Feng; Jia-Rui Han; Chun-Yan Lu; Li Gu; Shuai Li; Wen-Hui Lian; Lei Dong; Wen-Jun Li (Current Microbiology, 2023)

Nanoplastic-Induced Biological Effects In Vivo and In Vitro: An Overview - Hongxin Xie; Xue Tian; Xiaoying Lin; Rui Chen; Saima Hameed; Liming Wang; Yong-Liang Yu; Bai Li; Yu-Feng Li (Reviews of Environmental Contamination and Toxicology, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

A single-site porphyrin (Cu)-based COF electrocatalyst for the electrochemical detection of gallic acid sensitively - Mei-Jie Wei; Jing Li; Ze-Qi Wei; Sheng-Feng Zhang; Zhong-Xia Wang; Heng-Ye Li; Rui Zhang; Fen-Ying Kong; Wei Wang (Analytica Chimica Acta, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Phosphoproteomic Analysis Reveals the Predominating Cellular Processes and the Involved Key Phosphoproteins Essential for the Proliferation of Toxoplasma gondii - Xin-zhu Chen; Rui-xue Bai; Fei-yu Qin; Hong-juan Peng; Jin-feng Ren; Lang Hu; Yu-di Li; Cheng He (Acta Parasitologica, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

TBtools-II: A “one for all, all for one” bioinformatics platform for biological big-data mining - Chengjie Chen; Ya Wu; Jiawei Li; Xiao Wang; Zaohai Zeng; Jing Xu; Yuanlong Liu; Junting Feng; Hao Chen; Yehua He; Rui Xia (Molecular Plant, 2023)

Insights into brain perceptions of the different taste qualities and hedonic valence of food via scalp electroencephalogram - Tianyi Yang; Peng Zhang; Lidong Xing; Jin Hu; Rui Feng; Junjie Zhong; Weitao Li; Yizhi Zhang; Qiaoqiao Zhu; Yamin Yang; Fan Gao; Zhiyu Qian (Food Research International, 2023)

Synergetic effect on fouling alleviating of membrane distillation in urine resource recovery by thermally activated peroxydisulfate pretreatment - Yaping Lyu; Xiuwei Ao; Zongsu Wei; Shikun Cheng; Xiaoqin Zhou; Nana Liu; Xuemei Wang; Rui Feng; Zifu Li (Environmental Research, 2023)

Emissions and mitigation potential of endocrine disruptors during outdoor exercise: Fate, transport, and implications for human health - Rui Luo; Tao Zhang; Li Wang; Yong Feng (Environmental Research, 2023)

Insights into simultaneous adsorption of orthophosphate (PO43−) and 1-hydroxyethane 1,1-diphosphonic acid (HEDP) by kaolin/lanthanum carbonate composites: Experimental analysis and DFT calculations - Jun Wan; Rui Li; Xiaonan Feng; Jiazhi Yang; Yuxuan Ye; Sifeng Jian; Xiaowei Zhang (Chemical Engineering Journal, 2023)

Magmatic fluids responsible for lode gold mineralization in the giant Linglong deposit at Jiaodong, North China Craton: Constraints from LiO isotopes - Shao-Rui Zhao; Zhan-Ke Li; Zu-Wei Lin; Jian-Feng Gao; Hua-Shan Sun; Martin Yan Hei Li; Xin-Fu Zhao (Chemical Geology, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Insight into the effect of a heavy metal mixture on neurological damage in rats through combined serum metabolomic and brain proteomic analyses - Jie Xie; Fankun Zhou; Lu Ouyang; Qi Li; Shaoqi Rao; Rui Su; Shuo Yang; Jiajun Li; Xin Wan; Lingyu Yan; Peishan Liu; Hui Cheng; et al. (Science of The Total Environment, 2023)

Dynamic simulation and control strategy exploration of the unsafe behavior of coal mine employees - Wanzhen Li; Lujie Zhou; Jian Hao; Kai Yu; Jing Chen; Pingping Liu; Rui Feng (Resources Policy, 2023)

Symbiotic hemolymph bacteria reduce hexavalent chromium to protect the host from chromium toxicity in Procambarus clarkii - Cheng-Ming Yin; Rui-Geng Niu; Hui Wang; Xian-Yao Li; Qi-Fan Zeng; Jiang-Feng Lan (Journal of Hazardous Materials, 2023)

Zero-valent cobalt and oxygen vacancy rich catalyst derived from Ni/Co metal-organic framework nanosheets for enhanced oxidation of aqueous contaminants via peroxymonosulfate activation - Haodong Hu; Xinlong Yan; Qingxun Hu; Xiaoyan Hu; Rui Feng; Tianbo Li; Wei Zhou; Liping Wang (Journal of Environmental Chemical Engineering, 2023)

Simultaneous detection of heterocyclic aromatic amines and acrylamide in thermally processed foods by magnetic solid-phase extraction combined with HPLC-MS/MS based on cysteine-functionalized covalent organic frameworks - Yanmei Feng; Yiheng Shi; Rui Huang; Panpan Wang; Guoliang Li (Food Chemistry, 2023)

Effects of Lactiplantibacillus plantarum with different phenotypic features on the nutrition, flavor, gel properties, and digestion of fermented soymilk - Xueliang Zhang; Changliang Zhang; Luyao Xiao; Suying Wang; Xiaochan Wang; Kai Ma; Feng Ji; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Bioscience, 2023)

The mixed-order chlorine decay model with an analytical solution and corresponding trihalomethane generation model in drinking water - Weinan Feng; Wencheng Ma; Qijia Zhao; Feiyu Li; Dan Zhong; Liming Deng; Yisong Zhu; Zhaopeng Li; Ziyi Zhou; Rui Wu; Luming Liu; Jun Ma (Environmental Pollution, 2023)

Polyamide/UiO-66-NH2 nanocomposite membranes by polyphenol interfacial engineering for molybdenum(VI) removal - Zhenwei Wu; Jianxian Zeng; Zhengqiu Yuan; Rui Zhang; Xiaoping Huang; Fan Feng; Minjuan Chen; Kai Jin; Shengkai Yang; Yahong Li (Desalination, 2023)

A novel starch-based ethanol gel with contact-killing bacteria to cut off contact transmission of bacteria - Fu-Xiang Wei; Tian-Rui Zhou; Shao-Wei Zhong; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Chemical Engineering Journal, 2023)

The function of steroid terminal monooxygenase in cholesterol or phytosterol degradation by the Mycobacterium neoaurum NRRL B-3805 - Xuemei Li; Rui Zhang; Jianjiong Li; Jinhui Feng; Qiaqing Wu; Dunming Zhu; Yanhe Ma (Systems Microbiology and Biomanufacturing, 2023)

Realgar-Induced Neurotoxicity: Crosstalk Between the Autophagic Flux and the p62-NRF2 Feedback Loop Mediates p62 Accumulation to Promote Apoptosis - Rui Feng; Jieyu Liu; Zhao Yang; Tiantian Yao; Ping Ye; Xiuhan Li; Jiaxin Zhang; Hong Jiang (Molecular Neurobiology, 2023)

Effects of ferrous sulfate modification on the fate of phosphorous in sewage sludge biochar and its releasing mechanisms in heavy metal contaminated soils - Aikelaimu Aihemaiti; Shuoyang Liang; Yingying Cai; Rui Li; Feng Yan; Zuotai Zhang (Environmental Science and Pollution Research, 2023)

Preliminary horizontal co-seismic displacements caused by the 2023 Mw 7.8 and Mw 7.5 Türkiye earthquakes estimated using high-rate GPS observations - Feng Shengtao; Li Jie; Li Guirong; Li Rui; Sulitan Yusan; Aerdake Kadeerbieke (Acta Geophysica, 2023)

Spatiotemporal variations and dominated environmental parameters of nitrous oxide (N2O) concentrations from cascade reservoirs in southwest China - Chiquan He; Rui Qi; Haiyue Feng; Zhenzhen Zhao; Fushun Wang; Daoyuan Wang; Feifei Wang; Xueping Chen; Pu Zhang; Siliang Li; Yuanbi Yi (Environmental Science and Pollution Research, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

The Dynamics of Dopamine D2 Receptor-Expressing Striatal Neurons and the Downstream Circuit Underlying L-Dopa-Induced Dyskinesia in Rats - Kuncheng Liu; Miaomiao Song; Shasha Gao; Lu Yao; Li Zhang; Jie Feng; Ling Wang; Rui Gao; Yong Wang (Neuroscience Bulletin, 2023)

Expression and functional analysis of ace1 and ace2 reveal their differential roles in larval growth and insecticide sensitivity in Spodoptera frugiperda (J. E. Smith, 1797) - Jie Gao; Li-Feng Gong; Huan-Huan Wang; Rui Zhao; Xing Xiao; Xin-Yao Tian; Bo Li; Pei Liang; Xi-Wu Gao; Shao-Hua Gu (Journal of Pest Science, 2023)

Prediction of landslide block movement based on Kalman filtering data assimilation method - Yong Liu; Qing-jie Xu; Xing-rui Li; Ling-feng Yang; Hong Xu (Journal of Mountain Science, 2023)

Corrigendum to “Efficient lead immobilization by bio-beads containing Pseudomonas rhodesiae and bone char” [J. Hazard. Mater. 447 (2023) 130772] - Junpeng Li; Rui Bai; Wei Chen; Chongyuan Ren; Fan Yang; Xiaochun Tian; Xiaofeng Xiao; Feng Zhao (Journal of Hazardous Materials, 2023)

Emission factors of ozone-depleting chloromethanes during production processes based on field measurements surrounding a typical chloromethane plant in China - Bowei Li; Xingchen Zhao; Xinhe Li; Xiaoyi Hu; Liting Hu; Di Chen; Minde An; Yang Yang; Rui Feng; Liya Guo; Pengnan Jiang; Bo Yao; et al. (Journal of Cleaner Production, 2023)

Novel “all-in-one” multifunctional gelatin-based film for beef freshness maintaining and monitoring - Rui Li; Di Zhuang; Haoyu Feng; Shancan Wang; Jie Zhu (Food Chemistry, 2023)

Assessing the occurrence and sources of synthetic additive pollutants in lake sediments using fecal and sewage markers - Rui Du; Xiaoxia Feng; Pu Wang; Ruiqiang Yang; Gang Li; Jianjie Fu; Yong Liang; Ting Ruan; Guibin Jiang (Environmental Pollution, 2023)

Enlocking the high Zn2+-storage of conversion-type Te cathode by regulating the surface binding-interaction with graphene - Cong Guo; Shangjun Yi; Rui Si; Yixiao Wang; He Liu; Feng Yu; Jingfa Li (Chemical Engineering Journal, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

Effects of long-term warming on soil prokaryotic communities in shrub and alpine meadows on the eastern edge of the Qinghai-Tibetan Plateau - Wei Li; Lingchen Yuan; Xianli Lan; Rui Shi; Dongdong Chen; Defeng Feng; Xinquan Zhao; Huai Chen (Applied Soil Ecology, 2023)

Two new isoflavones from the barks of Dalbergia hancei Benth - Xiao-Mei Li; Nao Pang; Ya-Feng Wang; Rui-Jie He; Li Ge; Bing-Yuan Yang; Ke-Di Yang; Yong-Lin Huang (Natural Product Research, 2023)

Magnetic anaerobic granular sludge for sequestration and immobilization of Pb - Rui Zhou; Han Li; Chengshuai Liu; Yizhang Liu; Jyh-Fu Lee; Yu-Jung Lin; Zhang Yan; Zhangyi Xu; Xiaoyun Yi; Chunhua Feng (Water Research, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Mechanism for regulation of a forward osmosis membrane by the SA/UiO-66-NH2 composite interlayer and the resulting lithium ion concentration performance - Miaolu He; Yushuang Li; Leihao Feng; Jiaqi Wang; Ze Liu; Lei Wang; Jin Wang; Rui Miao; Xudong Wang (Journal of Cleaner Production, 2023)

Formation and preservation of ultra-deep liquid petroleum in the Ordovician sedimentary succession in Tarim Basin during the neotectonic phase - Feng Li; Xiuxiang Lü; Guangyou Zhu; Jianfa Chen; Rui Wang; Zhenghui Wu; Tao He; Nan Xue (Journal of Asian Earth Sciences, 2023)

Paleozoic remelting of carbonatite in Bayan Obo (China): Further insights into the formation of a giant REE deposit - Hai-Dong She; Hong-Rui Fan; M. Santosh; Xiao-Chun Li; Kui-Feng Yang; Qi-Wei Wang; Wei Wei; Yan-Jiang Liu; Shang Liu; Shuang-Liang Liu (Gondwana Research, 2023)

Insights into dissolved organics in non-urban areas - Optical properties and sources - Feng Yu; Xiaofei Li; Rui Zhang; Jingning Guo; Wen Yang; Lekhendra Tripathee; Lang Liu; Yuqin Wang; Shichang Kang; Junji Cao (Environmental Pollution, 2023)

Revealing the role of calcium alginate-biochar composite for simultaneous removing SO42− and Fe3+ in AMD: Adsorption mechanisms and application effects - Rui Li; Bing Wang; Pan Wu; Jian Zhang; Xueyang Zhang; Miao Chen; Xingxing Cao; Qianwei Feng (Environmental Pollution, 2023)

Structural characterization of a pectic polysaccharide from laoshan green tea and its inhibitory effects on the production of NO, TNF- α and IL-6 - Fan Liu; Rongshen Wang; Ying Chen; Rui Geng; Hong Gao; Feng Wang; Xiaoxiao Liu; Wanzhong Li (Natural Product Research, 2023)

Toxicity and synergistic effect of secondary metabolites isolated from the endophytic fungus LS-Y-1 of Rhododendron przewalskii against Tribolium castaneum - Junyu Liang; Haoshu Wu; Xudong Wang; Rui Feng; Peiyu Lu; Jie Xu; Weibao Kong; Yuan Li (South African Journal of Botany, 2023)

Differential effects of petroleum-based and bio-based microplastics on anaerobic digestion: A review - Zezhou Shang; Rui Wang; Xiyi Zhang; Yongle Tu; Chenjing Sheng; Huan Yuan; Lei Wen; Yulu Li; Jing Zhang; Xiaojiao Wang; Gaihe Yang; Yongzhong Feng; et al. (Science of The Total Environment, 2023)

Three new isoquinoline alkaloids from the cigar tobacco-derived endophytic fungus Aspergillus felis - Yue-Yu Ma; Gui Pu; Xue-Ju Cha; Rui-Feng Xiong; Guang-Hai Zhang; Heng Yao; Mei-Fen Bao; Guang-Hui Kong; Yin-Ke Li; Qiu-Fen Hu; Yu-Ping Wu (Phytochemistry Letters, 2023)

Experimental study on the movement law of overlying rock non-pillar coal overhead mining - Yong Li; Jing Zheng; Feng-nian Wang; Xin-gen Ma; Rui-xue Zhang; Ying-ying Sun; Jian-bin Yin; Zhi-gang Tao (Journal of Mountain Science, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

Short-term effect of apparent temperature on daily hospitalizations for osteoporotic fractures in Beijing, China: A retrospective observational study - Shuai Lu; Xuejiao Liu; Yanlin Niu; Feng Li; Maoqi Gong; Yejun Zha; Qingchen Chao; Bo Lu; Baichao Zhang; Ning Li; Jia Chen; Qiyong Liu; et al. (Science of The Total Environment, 2023)

Underestimation of biomass burning contribution to PM2.5 due to its chemical degradation based on hourly measurements of organic tracers: A case study in the Yangtze River Delta (YRD) region, China - Qing Li; Kun Zhang; Rui Li; Liumei Yang; Yanan Yi; Zhiqiang Liu; Xiaojuan Zhang; Jialiang Feng; Qiongqiong Wang; Wu Wang; Ling Huang; Yangjun Wang; et al. (Science of The Total Environment, 2023)

Diversity and distribution variation of urban spontaneous vegetation with distinct frequencies along river corridors in a fast-growing city - Xiaopeng Li; Sining Zhang; Rui Huang; Li Feng; Sihui Xu; Baichuan Liu (Journal of Environmental Management, 2023)

Prediction of vitrinite reflectance of shale oil reservoirs using nuclear magnetic resonance and conventional log data - Cheng Feng; Ziyan Feng; Rui Mao; Guanglei Li; Yuntao Zhong; Kegang Ling (Fuel, 2023)

Cognitive outcomes caused by low-level lead, cadmium, and mercury mixture exposure at distinct phases of brain development - Lu Ouyang; Qi Li; Shaoqi Rao; Rui Su; Yanhui Zhu; Guihua Du; Jie Xie; Fankun Zhou; Chang Feng; Guangqin Fan (Food and Chemical Toxicology, 2023)

A novel reduced graphene oxide/polypyrrole conductive ceramic membrane enhanced electric field membrane bioreactor: Mariculture wastewater treatment performance and membrane fouling mitigation - Rui Wang; Hong You; Zhipeng Li; Binghan Xie; Shaojie Qi; Jing Zhu; Qiqing Qin; Han Wang; Jinxu Sun; Yi Ding; Yuhong Jia; Feng Liu (Bioresource Technology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Forward osmosis membrane doped with water-based zirconium fumarate MOFs to enhance dye pollutant removal and membrane antifouling performance - Miaolu He; Leihao Feng; Qi Cui; Yushuang Li; Jiaqi Wang; Jiani Zhu; Lei Wang; Xudong Wang; Rui Miao (Environmental Science and Pollution Research, 2023)

Comparative transcriptomes analysis of the ovary reveals potential ovarian development-related genes and pathways in Macrobrachium rosenbergii - Yan-Hao Yang; Rui Wang; Ming Li; Hui-Zan Yang; Guang-Hua Huang; Ke-Yi Ma; Gao-Feng Qiu; Yong Lin (Invertebrate Reproduction & Development, 2023)

Endoplasmic reticulum stress regulates autophagic response that is involved in Saikosaponin a-induced liver cell damage - Ye-Feng Wang; Rui-Xia Ma; Bin Zou; Jia Li; Yao Yao; Juan Li (Toxicology in Vitro, 2023)

Efficient lead immobilization by bio-beads containing Pseudomonas rhodesiae and bone char - Junpeng Li; Rui Bai; Wei Chen; Chongyuan Ren; Fan Yang; Xiaochun Tian; Xiaofeng Xiao; Feng Zhao (Journal of Hazardous Materials, 2023)

Inhibition of human sulfotransferases (SULTs) by per- and polyfluoroalkyl substances (PFASs) and structure-activity relationship - Yong-Zhe Liu; Kai Yang; Wei Zhang; Qian zhang; Tong-Feng Liu; Tong Xu; Yang Li; Rui-Xue Ran; Kun Yang; Yun-Feng Cao; Zhong-Ze Fang (Food and Chemical Toxicology, 2023)

New insights into photochemical initial concentrations of VOCs and their source implications - Bowei Li; Shaocai Yu; Min Shao; Xinhe Li; Steven Sai Hang Ho; Xiaoyi Hu; Hongli Wang; Rui Feng; Xuekun Fang (Atmospheric Environment, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Molecular Hydrogen: an Emerging Therapeutic Medical Gas for Brain Disorders - Chongyun Wu; Peibin Zou; Shu Feng; Ling Zhu; Fanghui Li; Timon Cheng-Yi Liu; Rui Duan; Luodan Yang (Molecular Neurobiology, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Determination and prediction of digestible energy, metabolizable energy, and standardized ileal digestibility of amino acids in barley for growing pig - Rui Li; Mingzhou Tian; Ganyi Feng; Gaifeng Hou; Xianji Jiang; Gang Yang; Qiang Xiang; Xiaojie Liu; Cimi Long; Ruilin Huang; Yulong Yin (Animal Feed Science and Technology, 2023)

Tunable nanochannel resistive pulse sensing device using a novel multi-module self-assembly - Wenwei Pan; Rui You; Shuaihua Zhang; Ye Chang; Feng Zhou; Quanning Li; Xuejiao Chen; Xuexin Duan; Ziyu Han (Analytica Chimica Acta, 2023)

Pulsed turbidite and methane seep records in the north western South China Sea since the last glacial maximum - Jingrui Li; Xiaoming Miao; Xiuli Feng; Rui Jiang; Mengwei Zhao; Xiaopeng Dan; Qianwen Xiao; Jiangong Wei (Frontiers in Marine Science, 2023)
The small-scale event layers in the continental margin contain abundant dynamic environment information, and pose a challenge to the interpretation of continuous sedimentary records, giving geological significance to their accurate identify and possible genesis. Here, pulsed turbidite layers since the last glacial maximum (LGM) in a gravity core in the northwestern South China Sea (SCS) was analyzed to investigate the precisely identification, possible causes and the role of marine environmental change during the late Quaternary in formation of these small-scale event layers in the SCS. Eight potential pulsed turbidite layers, according to the petrographic characteristics, grain size parameters and element geochemistry, were identified. Meanwhile, indicators including total sulfur (TS)/total organic carbon (TOC) ratio, CaCO 3 content, and chromium-reducible sulfur (CRS) revealed these horizons were mostly related to methane seep events. Constrained by foraminifera shells AMS 14 C results, these events were determined to have occurred from the LGM to early Holocene, Similar records in the northern and southern slopes suggests the universal occurrence of these small-scale layers in the SCS. The comprehensive analysis showed that the development of these event layers over the past 25 ka can be divided into three stages, 25-15.5 ka, 15.5-7 ka and 7 ka to present. Late Quaternary Ocean environment changes, especially sea level and bottom water temperature, controlled the occurrence of regional small-scale event layers in the SCS. The regional scale mechanism is that the pressure and temperature change affect the stability of hydrate and the methane seepage, and thus the strata stability. Corresponding to the lowest, the rapid increase and the highest levels of the sea level and bottom water temperature, the temporal evolution pattern of small-scale event layers in the SCS showed a highest, decreased and lowest frequency, respectively. The linkage between the late Quaternary marine environmental change and turbidite deposition through gas activities in this study can act as a useful reference for further understanding the continental margin sedimentary process.

Tailoring enzymatic loading capacity on CdS nanorods@ZnIn2S4 nanosheets 1D/2D heterojunctions: Toward ultrasensitive photoelectrochemical bioassay of tobramycin - Rui Hu; Ben-Fang Xu; Yadong Xue; Zhi-Zhi Xu; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemosphere, 2023)

Creation of intermuscular bone-free mutants in amphitriploid gibel carp by editing two duplicated runx2b homeologs - Rui-Hai Gan; Zhi Li; Zhong-Wei Wang; Xi-Yin Li; Yang Wang; Xiao-Juan Zhang; Jin-Feng Tong; Yue Wu; Ling-Yun Xia; Ze-Xia Gao; Li Zhou; Jian-Fang Gui (Aquaculture, 2023)

Characteristics and source apportionment of some halocarbons in Hangzhou, eastern China during 2021 - Xinhe Li; Bowei Li; Yang Yang; Liting Hu; Di Chen; Xiaoyi Hu; Rui Feng; Xuekun Fang (Science of The Total Environment, 2023)

Infant food production environments: A potential reservoir for vancomycin-resistant enterococci non-nosocomial infections - Zining Wang; Sihao Liao; Guanwen Huang; Mengyao Feng; Rui Yin; Lin Teng; Chenghao Jia; Yicheng Yao; Min Yue; Yan Li (International Journal of Food Microbiology, 2023)

Pregnancy and lactation mixed exposure to lead, cadmium, and mercury alters maternal-offspring single heavy metal load: A factorial design - Guihua Du; Fankun Zhou; Lu Ouyang; Kai Wang; Shaoqi Rao; Rui Su; Yanhui Zhu; Kechu Guo; Jinmei Xiao; Jie Xie; Qi Li; Chang Feng; et al. (International Journal of Hygiene and Environmental Health, 2023)

Effects of Alpine Grassland Degradation on Soil Microbial Communities in Qilian Mountains of China - Chunming Li; Derong Zhang; Gengchun Xu; Rui Yan; Yang Huang; Liuqing Feng; Jin Yi; Xiangyu Xue; Huixia Liu (Journal of Soil Science and Plant Nutrition, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Isolation of atrazine nanobodies enhanced by depletion of anti-carrier protein phages and performance comparison between the nanobody and monoclonal antibody derived from the same immunogen - Qingqing He; Mian Wang; Yajie Zhao; Guiyu Tan; Man Zhang; Rui Feng; Yujie Chen; Baomin Wang; Qing X. Li (Analytica Chimica Acta, 2023)

Selenium alleviates endoplasmic reticulum calcium depletion-induced endoplasmic reticulum stress and apoptosis in chicken myocardium after mercuric chloride exposure - Pei-Chao Gao; An-Qi Wang; Xue-Wei Chen; Han Cui; Yue Li; Rui-Feng Fan (Environmental Science and Pollution Research, 2023)

Rockburst and microseismic activity in a lagging tunnel as the spacing between twin TBM excavated tunnels changes: A case from the Neelum-Jhelum hydropower project - Peng-Xiang Li; Bing-Rui Chen; Ya-Xun Xiao; Guang-Liang Feng; Yang-Yi Zhou; Jin-Shuai Zhao (Tunnelling and Underground Space Technology, 2023)

Microbial-induced calcium carbonate precipitation: Influencing factors, nucleation pathways, and application in waste water remediation - Yu Liu; Amjad Ali; Jun-Feng Su; Kai Li; Rui-Zhu Hu; Zhao Wang (Science of The Total Environment, 2023)

Manganese-induced α-synuclein overexpression promotes the accumulation of dysfunctional synaptic vesicles and hippocampal synaptotoxicity by suppressing Rab26-dependent autophagy in presynaptic neurons - Zhuo Ma; Kuan Liu; Rui-feng Zhang; Zi-xin Xie; Wei Liu; Yu Deng; Xin Li; Bin Xu (Science of The Total Environment, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Microwave-assisted co-precipitation preparation of CuFe2O4 photo-Fenton degradation tetracycline: Characterization, efficacy, stability in complex water quality and mechanism - Xiyu Sun; Guangzhi Wang; Likun Huang; Huanzhang Feng; Simin Zhou; Rui Zhao; Dongdong Wang; Zhe Li (Journal of Environmental Chemical Engineering, 2023)

Pioneering observation of atmospheric volatile organic compounds in Hangzhou in eastern China and implications for upcoming 2022 Asian Games - Bowei Li; Steven Sai Hang Ho; Xinhe Li; Liya Guo; Rui Feng; Xuekun Fang (Journal of Environmental Sciences, 2023)

Expanded polystyrene buoys as an important source of hexabromocyclododecanes for aquatic ecosystem: Evidence from field exposure with different substrates - Yun-Feng Pan; Shan Liu; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Environmental Pollution, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

The protective effect of Eleutheroside E against the mechanical barrier dysfunction triggered by lipopolysaccharide in IPEC-J2 cells - Huijuan Li; Rui Han; Feng Yong; Yueli Fan; Bao Zhao; Xiaocai Hu; Tianrui Zhang; Dongsheng Che (Research in Veterinary Science, 2023)

Mechanism of excavation-induced cracking of the protective layer of a rock bench in a large underground powerhouse under high tectonic stress - Yuelin Xia; Xia-Ting Feng; Chengxiang Yang; Shaojun Li; Dingping Xu; Quan Jiang; Rui Kong; Yonghong Li; Zhiguo Li (Engineering Geology, 2023)

Characteristics of non-point source pollution based on monitoring experiment in the Yingwugou small watershed, China - Kai Peng; Jia-ke Li; Gai-rui Hao; Yi-wen Liu; Xiang Zhou; Wei-feng Xie (Ecohydrology & Hydrobiology, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

Temperature-gradient-induced enhanced fog collection on polymer brush surfaces - Zheng-Hong Liang; Rui Feng; Jia-Min Wu; Dong Li; Fang Wang; Xiu-Li Wang; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

Formation mechanism and metabolic pathways of photogranule in batch and continuous-flow mode under high salinity stress - Jing Zhu; Hong You; Zhipeng Li; Binghan Xie; Weirun Li; Shaojie Qi; Rui Wang; Hongying Chen; Binyu Ma; Yi Ding; Haili Tan; Feng Liu; et al. (Chemical Engineering Journal, 2023)

Water-soluble brown carbon in PM2.5 at two typical sites in Guanzhong Basin: Optical properties, sources, and implications - Xiaofei Li; Feng Yu; Yiying Song; Chao Zhang; Fangping Yan; Zhaofu Hu; Yali Lei; Lekhendra Tripathee; Rui Zhang; Jingning Guo; Yuqin Wang; Qingcai Chen; et al. (Atmospheric Research, 2023)

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

Evaluating the effects of contact time and leaching solution on measured solubilities of aerosol trace metals - Rui Li; Shuwei Dong; Chengpeng Huang; Feng Yu; Fu Wang; Xiaofei Li; Huanhuan Zhang; Yan Ren; Mingxian Guo; Qingcai Chen; Baozhu Ge; Mingjin Tang (Applied Geochemistry, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)